Civil engineering design project technical report - Ismail, Muhammad Iqbal Hakim (2024)
In conclusion, the imperative nature of creating detailed architectural drawings before commencing construction cannot be overstated. As part of their final year project, students are tasked with not only sourcing architectural drawings for a single-story house but also developing a comprehensive project timeline. Moreover, they are required to craft key plans for each level, adhering to the referenced Eurocode 2 standard. It is crucial to meticulously locate and assess the designated regions for reinforcement in the chosen structural components to ensure structural integrity and prevent any potential failures. The subsequent step involves the calculation of the Bill of Quantities through the taking-off approach. However, the intricacies of structural calculations necessitate a comparison between manual calculations and software-generated results, particularly using tools like ESTEEM. Notably, ESTEEM utilizes distinct formulas, such as Wood & Amer's formula, which can yield variations in results. The examination of these differences is paramount, as demonstrated in the preceding slide, revealing discrepancies exceeding 20% in certain instances. This emphasizes the importance of validating manual calculations against software outputs to enhance accuracy in structural assessments. Lastly, the successful completion of the project assignment relies on the assimilation and application of knowledge acquired from courses like Civil Engineering Design Project (ECS 358), Structural Concrete and Steel Design (ECS 338), and Civil Engineering Quantities and Estimation (ECM366). The benefits derived from these studies extend beyond academic pursuits, serving as valuable assets during industrial training or within the professional work environment. This holistic approach ensures that students not only fulfill academic requirements but also equip themselves with practical skills essential for their future endeavors in the field of civil engineering.